Pengembangan Game Multiplayer Horror 'Angker' Berbasis Mobile Menggunakan Metode Agile - Apik Banyubasa; Cindy Valencia; Hassan Narallah Matauq; R Bramaditya Ario Wirawisesa; Aditya Wicaksono; Muhammad Nasir (J-INTECH ( Journal of Information and Technology), 2025)
This study develops a mobile-based multiplayer horror game titled "Angker" using the Agile method, specifically Agile Scrum, in response to the rapid growth of the mobile game industry and increasing interest in the multiplayer horror genre. The Agile method was chosen for its flexibility in managing complex game development, allowing quick adaptation to changes and strong team collaboration. The development process was divided into eight sprints, covering planning (team role assignment, project scheduling), design (UML diagrams, UI design using Figma), feature development (character movement, multiplayer system, chat, item system, visual/audio assets, in-game store, skin transactions), internal and external testing, and final deployment. A total of 15 core features were successfully developed and implemented, including 8 technical modules such as a multiplayer lobby system, coin transaction system, interactive item system, and win condition detection system. Testing results demonstrated improvements in time efficiency, team coordination, and final product quality. The novelty of this study lies in the comprehensive integration of the Agile method in multiplayer horror game development using the Godot engine—an approach still rarely implemented, especially by small teams with limited resources.